KARAKTERISASI BIJI DAN PROTEIN KORO KOMAK (Lablab purpureus (L.) Sweet) SEBAGAI SUMBER PROTEIN [Characterization of Hyacinth Bean (Lablab purpureus (L.) Sweet) Seed and Its Protein] - Andrew S R; Wiwiek S W; A Subagio (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2006)
This research aimed to characterize the physiochemical properties of hyacinth beans as new protein source. The result of research showed that hyacinth beans are oval shaped and orange and yellow coloured. The edible part of hyacinth beans is 83.2 ± 1.1 % of dry seed; in which the carbohydrate is 67.9 ± 1.1 %; protein: 17.1 ± 1.5 % and fat: 1.1 ± 0.4 %. According to their solubility, the protein fractions were found as albumin: 18.22 %; globuli : 55.15 % and glutelin : 26.13 %, whereas prolamin was not detected. Further analyis showed that, the globulin is consisted of globulin 7S (3.50%) and globulin 11S (0.67 %). The hyacinth beans are potential to be used for protein source. Key words: hyacinth beans, physiochemical properties, protein fractions, seed protein.